Green house studies on the biology of winter annual grasses and the use of cover crops and herbicides for their control - Ranjit, JD; Bellinder, R; Benidict, C; Kumar, V (Agronomy Journal of Nepal, 2013)
Greenhouse studies were initiated in two small (Polypogon fugox) and large (Phalaris minor) seeded annual grasses in 2007 at Cornell University, Ithaca, NY USA. These two annual grasses were very common in wheat fields of midhills and terai regions of Nepal. P fugox was taken for biological study. Days to emergence took 8-11 days in green house. Early emerged panicles were longer than those emerged late. Panicle took 10-12 days to emerge completely from the flag leaf. Panicles per plant were 120. Seeds were very small having about 1091 seeds per panicle. So one fully matured plant could produce seeds about 130920. Study on eco-biology needs to continue in the future. P fugox and P minor responded differently to buckwheat residues. Among different treatments emergence and growth of both weeds were suppressed more by buckwheat residues when left on the surface than incorporated. P minor was less affected by buckwheat residues. It might be due to larger seed compared to P fugox. Post emergence herbicides clodinofop and pinoxaden were effective on both grasses. Isoproturon and tralkoxydim were effective on P fugox. Sulfosulfuron was good in reducing plant growth to some extent. Preemergence herbicides pendimethalin and s-metolochlor were effective in reducing emergence and growth of both weeds. Isoproturon and and sulfosulfuron suppressed plant growth reducing dry plant biomass. DOI: http://dx.doi.org/10.3126/ajn.v2i0.7529 Agronomy Journal of Nepal (Agron JN) Vol. 2: 2011 pp.139-148